Targeted RNAi of the mitogen-activated protein kinase pathway genes in acute myeloid leukemia cells - Mohd Hafiz, M.R.; Mazatulikhma, M.Z.; Mohd Faiz, F.A.; Mohamed Saifulaman, M.S. (Universiti Kebangsaan Malaysia, 2013)
In this study, RNA interference (RNAi) was carried out as an experimental technique to knockdown three mitogen-activated protein kinase (MAPK) pathway genes, raf-1, mekk1 and mlk3 in acute myeloid leukemia (AML) cells. Conventionally, RNAi knockdown experiments target a single gene for functional studies or therapeutic purposes. We wanted to explore the potential differences or similarities between targeting single targets or multiple target genes in a single application. We achieved knockdown of gene expression levels of between 40 and 60% for the RNAi experiments, with better knockdown observed in single target gene experiments in comparison with the multiple target gene experiment. Microarray analysis indicated that the transfection process had most likely induced the immune response from the cells in every RNAi treatment. This might indicate that when the MAPK signaling pathway is partially blocked, in tandem with the immune response, the cells will begin signaling for apoptosis leading to cellular death of the leukemic cells.